2012
DOI: 10.1159/000335825
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Point Localization Varies Among Acupuncturists

Abstract: Background: Studies assessing the point-specific effect of acupuncture or the characteristics of acupuncture points (APs) tend to yield inconclusive results. In order to identify a possible confounding factor, we aimed to examine the variability in AP localization by means of a survey. Material and Methods: Attendees of the 14th ICMART (International Council of Medical Acupuncture and Related Techniques) congress as well as DÄGfA (German Medical Society of Acupuncture) lecturers and students were asked to loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This begs the question whether the traditional concept of an acupuncture point does indeed exist, and what, if any, is its significance. Notwithstanding the fact that there is a considerable variation between practitioners in localisation of individual points 13 , the lack of understanding of acupuncture's mechanism and whether this is point-specific has hampered ongoing efforts in defining acupoint relevance. Recent neuroimaging research appears to indicate that there is, indeed, a difference in cerebral activation patterns between acupuncture at verum points and random skin 22 , but there is a need for further work in this area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This begs the question whether the traditional concept of an acupuncture point does indeed exist, and what, if any, is its significance. Notwithstanding the fact that there is a considerable variation between practitioners in localisation of individual points 13 , the lack of understanding of acupuncture's mechanism and whether this is point-specific has hampered ongoing efforts in defining acupoint relevance. Recent neuroimaging research appears to indicate that there is, indeed, a difference in cerebral activation patterns between acupuncture at verum points and random skin 22 , but there is a need for further work in this area.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials comparing verum and sham acupuncture frequently employ very similar techniques, including the use of needles 4 . Although earlier trials have compared the points described during acupuncture performed at Traditional Chinese Medicine (as verum) with acupuncture at other skin sites (as sham) [9][10][11][12] , recent research suggests that acupuncture point localisation is not uniform between practitioners 13 , and that this lack of precision may contribute to the variability in trial outcomes 14 . Some trials have utilised modified needles 15 , or needling with minimal pressure 16,17 as sham, but the lack of a generally-accepted mechanism as to how acupuncture works has resulted in uncertainty in interpreting the results of these trials 4 .…”
Section: Challenges In Sham Acupuncture Deliverymentioning
confidence: 99%
“…The AP Lu11 has a clear anatomical localization, in contrast to numerous other APs which are much more difficult to localize [7][8][9]. This anatomical identification was, however, crucial to match the AP with the described changes of Cx density.…”
Section: Discussionmentioning
confidence: 97%
“…These treatment programs also vary based on different clinical experiences, styles, and schools. Above this, studies showed that even if the same points were chosen in theory, point locations still varied between doctors [ 67 ].…”
Section: Discussionmentioning
confidence: 99%